The pedagogy of competences in the Institutional Pedagogical Political Project of the Federal Institute of Education, Science and Technology of Ceará: a brief analysis (Research, Society and Development, 2020)
The objective of this article is to make a correlation between the pedagogy of competences and the pedagogy of competences and the political pedagogical project of the Federal Institute of Education Science and Technology of Ceará. This study discusses the relationship between the Institutional Pedagogical Political Project of the Federal Institute of Professional and Technological Education of Ceará (IFCE) and the pedagogy of competences, through works developed by authors of the human capital theory, of the critical analyzes carried out by renowned authors such as Marise Ramos, Gaudêncio Frigotto, Demerval Saviani, Acácia Zeneida Kuenzer and Silvia Maria Manfredi, as well as through the ideas of Philippe Perrenoud, the main exponent of this pedagogical theory. In methodological terms, the research is classified as a documentary bibliography. The results pointed out the intrinsic relationship between the development of skills pedagogy, the changes in the productive model that started in the second half of the 20th century and the discussions developed by the theory of human capital. It was also possible to observe the strong presence of the mentioned pedagogical theory in the laws that guide and regulate Brazilian education, specifically, professional and technological education. Finally, it was concluded that the Institutional Pedagogical Political Project of IFCE has principles of pedagogy of competences, which is consistent with studies on the insertion of the aforementioned pedagogical theory in Brazilian professional and technological education.